2008
DOI: 10.1177/1074248408318628
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Extra-Lipid Effects of Rosuvastatin

Abstract: Statins, in addition to their beneficial lipid modulation effects, exert a variety of several so-called "pleiotropic" actions that may result in clinical benefits. Rosuvastatin, the last agent of the class to be introduced, has proved remarkably potent in reducing low-density lipoprotein cholesterol levels. At present, no large-scale primary or secondary prevention clinical trials document either its long-term safety or its effectiveness in preventing cardiovascular events. A substantial number of experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 131 publications
(257 reference statements)
2
55
0
8
Order By: Relevance
“…In fact, titer of autoantibodies to ox-LDL was an independent predictor of the progression of carotid atherosclerosis in Finnish men [26]. In the previous studies, both rosuvastatin and fenofibrate have been associated with reduced ox-LDL levels [3,12,14,27]. Specifically, in a previous study, fenofibrate-associated ox-LDL reduction was greater in patients with high baseline ox-LDL levels, which was also the case in our study [14].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In fact, titer of autoantibodies to ox-LDL was an independent predictor of the progression of carotid atherosclerosis in Finnish men [26]. In the previous studies, both rosuvastatin and fenofibrate have been associated with reduced ox-LDL levels [3,12,14,27]. Specifically, in a previous study, fenofibrate-associated ox-LDL reduction was greater in patients with high baseline ox-LDL levels, which was also the case in our study [14].…”
Section: Discussionsupporting
confidence: 79%
“…Treatment with statins has been associated with improved outcomes either in the primary or in the secondary prevention of CVD [2]. This benefit has been attributed not only to the lipid-lowering potency, but also to various pleiotropic antiatherosclerotic properties of these drugs (namely antiinflammatory, antioxidative and antithrombotic) [3]. Oxidative stress, mostly by giving rise to endothelial dysfunction and pro-inflammatory processes, plays a major role in atherogenesis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosuvastatin-elicited vasodilatation was mediated by the production of NO and the opening of Ca 2+ -dependent K + channels of the Slow subfamily (7). Several protective effects of this statin related to its vascular effects have been demonstrated, including the prevention of inflammation and endothelial glycocalyx damage elicited by metalloproteinases, the inhibition of smooth muscle cell proliferation, the production of oxidized low-density lipoprotein, and an increase in plaque stability (13,14).…”
mentioning
confidence: 99%
“…It was found that some amino acids can prevent deposition of pre-atherogenic cholesterol in the arterial wall and reduce the risk of atherothrombosis, diabetes, and atherosclerosis [6]. Thus, amino acid leucine stimulates the production of insulin by the pancreas, which leads to normoglycemia in the blood of diabetic patients [5].…”
mentioning
confidence: 99%